2021
DOI: 10.1177/09721509211049890
|View full text |Cite
|
Sign up to set email alerts
|

Green Organizational Culture: An Exploration of Dimensions

Abstract: Awareness of environmental issues and stakeholder expectations has led organizations to be concerned about the impact of their products, processes and packaging on the natural environment. Environmental sustainability has become an essential tool for the competitive advantage of firms. Organizations need to bring about cultural transformation to sustain competitive advantage. This orientation has brought green organizational culture to centre stage as firms seek to institutionalize and incorporate environmenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…In addition, environmental responsibility is central to the business's survival and profit. These study results align with prior work by Gürlek and Tuna (2018), Kim (2020), Aggarwal andAgarwala (2021), andShah et al (2021), who all reported that OA as a firm goal is accomplished through green culture and personal environmental orientation.…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, environmental responsibility is central to the business's survival and profit. These study results align with prior work by Gürlek and Tuna (2018), Kim (2020), Aggarwal andAgarwala (2021), andShah et al (2021), who all reported that OA as a firm goal is accomplished through green culture and personal environmental orientation.…”
Section: Figuresupporting
confidence: 89%
“…Bauer and Aiman-Smith (1996) found that an organization's proactive stance on the environment is positively associated with OA, acceptance of job offers, and an intention to pursue employment with that organization. Following Aggarwal and Agarwala (2021), Gürlek and Tuna (2018), Kim (2020), andShah et al (2021), we propose that OA as a firm goal can be accomplished through a green culture and personal environmental orientation. H4: Green culture has a positive influence on OA H5: Personal environmental orientation has a positive influence on OA…”
Section: Organizational Reputation (Or) and Organizational Attractive...mentioning
confidence: 99%
“…Wang (2019) defined organizational culture as a shared system of values, beliefs, ideas and attitude that shape the organizational behavior. Culture helps the organization in transforming Relationship of GHRM with EP and GOC's effect the thinking of employees (Rao and Holt, 2005) and acts as a competitive advantage for an organization (Aggarwal and Agarwala, 2021;Shah et al, 2021). Harris and Crane (2002) defined GOC as an extent to which assumptions, values, symbols and artifacts of the organization reflect the desire to operate in an environmentally sustainable manner.…”
Section: Green Organizational Culturementioning
confidence: 99%
“…Dangelico (2015) suggested that organizations have to take conscious efforts to involve and develop all the organizational members to solve environmental problems that eventually lead to improved EP of the organization. Harris and Crane's (2002) model of green culture helps the organization in identifying where (degree, depth and diffusion) the environmental management efforts should be incorporated in the organization to lead a sustained business advantage (Aggarwal and Agarwala, 2021). demonstrated that the enablers of GOC (leadership emphasis, message credibility, and peer involvement and employee empowerment) provide a foundation for the improvement of green competitiveness of the firm.…”
Section: Dimensions Of Goc and Epmentioning
confidence: 99%
See 1 more Smart Citation